Chapter Internationalisation in Higher Education: A Virtual Adult Education Academy in Times of COVID-19 - Danquah, Jennifer (Studies on Adult Learning and Education, 2023)
COVID-19 calls for new ways of approaching internationalisation in adult learning and education. Based on experiences gathered during the 2021 virtual Adult Education Academy, this paper identifies challenges in international virtual learning settings in higher education. Such settings involve different levels of digital literacy among participants and moderators, limited access to high-speed internet, different time zones, and difficulties in social interactions. The article presents the didactical and methodological conceptualisation of a virtual setting to overcome these challenges. The concept involves facilitating exchanges between moderators, providing technical support, implementing (a-)synchronous sessions, and establishing a virtual space in which learning materials are created.